2003
DOI: 10.1007/s00221-003-1614-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-fos in auditory and non-auditory brain regions of the gerbil after manipulations that induce tinnitus

Abstract: Subjective tinnitus is a phantom sound sensation that does not result from acoustic stimulation and is audible to the affected subject only. Tinnitus-like sensations in animals can be evoked by procedures that also cause tinnitus in humans. In gerbils, we investigated brain activation after systemic application of sodium salicylate or exposure to loud noise, both known to be reliable tinnitus-inductors. Brains were screened for neurons containing the c-fos protein. After salicylate injections, auditory cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
98
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 30 publications
9
98
1
Order By: Relevance
“…Using c-fos and 2-DG-experiments, Wallhäusser-Franke et al (2003 and Wallhäusser-Franke (1997) were able to show that after noise trauma and the application of ototoxic drugs in animals known to result in tinnitus such a salicylate, there was a reduction in auditory nerve and cochlear nucleus activity and an elevation of auditory cortex activity. Müller et al (2003) found a reduction in the mean spontaneous firing rate at the level of the auditory nerve after salicilate intoxication.…”
Section: How Can This Results Be Interpreted In Light Of Existing Modementioning
confidence: 99%
“…Using c-fos and 2-DG-experiments, Wallhäusser-Franke et al (2003 and Wallhäusser-Franke (1997) were able to show that after noise trauma and the application of ototoxic drugs in animals known to result in tinnitus such a salicylate, there was a reduction in auditory nerve and cochlear nucleus activity and an elevation of auditory cortex activity. Müller et al (2003) found a reduction in the mean spontaneous firing rate at the level of the auditory nerve after salicilate intoxication.…”
Section: How Can This Results Be Interpreted In Light Of Existing Modementioning
confidence: 99%
“…In the case of tinnitus, enhanced activity of the amygdala is evidenced by c-fos expression in animal models (90,91), by source-localized electroencephalography (9), by positron emission tomography imaging (92), and by transient tinnitus diminution after suppression of the amygdalohippocampal complex by amytal (93). Hippocampal deficits have been documented in animal models of tinnitus and structural imaging in tinnitus patients has demonstrated a decrease in gray matter in the hippocampus (94).…”
Section: Phantom Percepts and Memorymentioning
confidence: 99%
“…One area receiving considerable attention is the auditory brainstem, in particular the dorsal cochlear nucleus (DCN) (Kaltenbach et al, 2005). However, the rostral brainstem, forebrain auditory structures, and nonauditory structures, such as the amygdala (AMYG), have also been implicated in the pathophysiology of tinnitus (Eggermont and Roberts, 2004;Lockwood et al, 2002;Norena et al, 2003b;Wallhausser-Franke et al, 2003). Evaluation of tinnitus mechanisms would be improved by examining relevant brain regions in subjects with a known and controlled etiology.…”
Section: Introductionmentioning
confidence: 98%